PENAMBAHAN EKSTRAK KULIT BUAH NAGA KE DALAM PENGENCER TRIS KUNING TELUR UNTUK MENINGKATKAN KUALITAS SEMEN BEKU KAMBING PERANAKAN ETTAWA - Bowo Siswandoko; Siti Zaenab; Husamah Husamah (Fakultas Biologi | Universitas Jenderal Soedirman, 2017)
The success of artificial insemination is determined by the quality of the frozen semen used. Free radicals and cold shock may reduce the quality of frozen semen. These can be prevented or reduced by the addition of antioxidants. Dragon fruit skin extract is rich in natural antioxidants. This study is aimed to analyze the effect of the addition of dragon fruit skin extract on quality (motility, viability, and abnormality) of frozen goat semen. The most effective concentration in frozen semen. The true experimental research was used with the posttest-only control group design. Data analysis was done by using One Way ANOVA followed by Duncan's test of 0.5% assisted by SPSS 22. The research was conducted in May–June 2017 at BBIB Singosari, Malang. The result showed that 0.50% concentration gave the highest motility (26.00 ± 6.51%) and the lowest abnormality (5.6 ± 2.7%), while at 0.75% gave the highest viability (61.60 ± 8.11%). It can be concluded that there is a significant effect (p < 0.05) addition of dragon fruit’s rind extract to the frozen semen quality (motility, viability, and abnormality) of ettawa goat and the most effective extract concentration varies on each quality parameter.